The importance socio-scientific issues of in biology learning preparing students as a 21st century society. Issue 2 (February 2019) - Nurtamara, L; Sajidan; Suranto
Abstract: The purpose of 21st Century Education is to prepare students as societies by empowerment high order thinking skills, such as constructs arguments and decision making based on the evidence of Socio-scientific Issues (SSI). However, most teachers have limited experience in teaching SSI in their classes. Research learning through SSI to help limited experience in the teaching SSI has grown in various countries by raising issues related to learning materials in the society case. Literature review studies about SSI in biology learning research are needed to provide recommendation SSI approach in biology learning for preparing students in 21st Century societies.